THE PERFORMANCE OF CARE: ETHNO-AESTHETIC TRADITIONS AND SUSTAINABLE GERIATRIC WELLBEING IN ASSAM’S CULTURAL LANDSCAPE - Das, Dimpy Pathak; Baruah, Samannoy (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The study provides a conceptual investigation of the elderly care within the cultural aesthetics and sustainability. Within the framework of a rapidly ageing society and growing burden on institutional systems of care, especially in culturally diverse areas such as Assam, the paper redefines care outside clinical constructs. Although home-based healthcare is becoming more and more cost-effective and is easily accessible, it may not bring an emotional dimension, cultural sensitivity, and holistic involvement. The paper has introduced the concept of performance of care in which ethno-aesthetic traditions, including music, storytelling, folk practices and visual art, are incorporated into geriatric care at home. Using the interdisciplinary literature, the study establishes a conceptual framework within which the engagement in aesthetics is related to better physical, emotional, and cognitive wellbeing in the elderly. It also puts this model in a sustainability paradigm, which focuses on economic viability, inclusion of the social, and conservation of the local cultural legacy in the Assamese environment. The paper suggests a solution to a more humane, culturally embedded and sustainable approach to geriatric wellbeing by connecting healthcare practices to cultural performance. The research provides rich information to policymakers, caregivers and researchers who wish to come up with inclusive and culture responsive elderly care models.